Fuel cell microporous catalyst layer for space power supply and preparation method of fuel cell microporous catalyst layer

By using gradient distribution catalysts and microporous catalytic layers of ladder distribution in fuel cells, the problem of water flooding in the fuel cell is solved, and the orientation flow and battery performance of the catalytic layer are improved.

CN119340401AInactive Publication Date: 2025-01-21SHENZHEN ACAD OF AEROSPACE TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411383103.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When using pure oxygen in existing space hydroxide fuel cells, the aquatic products in the reaction zone cannot be discharged in time, resulting in water flooding problems and affecting the mass transfer of the catalytic layer and battery performance.

Method used

A microporous catalytic layer, including anode and catalyst catalyst slurry, catalyst paste contains PT/metal oxide catalysts and I RO2-PT/metal oxide catalysts. The mass ratio of the vector and metal oxide carrier is also distributed in gradient.

Benefits of technology

It realizes the directional flow of water in the catalytic layer, enhances the water management ability of the membrane electrode under space microgravity conditions, improves the drainage capacity and power density of the battery, and extends the life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340401A_ABST
    Figure CN119340401A_ABST
Patent Text Reader

Abstract

The invention relates to the field of fuel cells, in particular to a fuel cell microporous catalyst layer for a space power supply and a preparation method of the fuel cell microporous catalyst layer. Cathode catalyst slurry comprises a Pt / metal oxide catalyst, a perfluorosulfonic acid ionomer, ultrapure water and isopropanol; the anode catalyst slurry comprises an I < r > O < 2->-Pt / metal oxide catalyst, a perfluorosulfonic acid ionomer, ultrapure water and isopropyl alcohol; the particle sizes of the Pt / metal oxide catalyst and the I rO2-Pt / metal oxide catalyst in the catalyst layer are distributed in a gradient manner; the mass ratio of the perfluorosulfonic acid ionomer to the metal oxide carrier in the catalyst layer of the anode catalyst slurry and the cathode catalyst slurry is in gradient distribution, and the mass ratio of the perfluorosulfonic acid ionomer to the ultrapure water and the mass ratio of the perfluorosulfonic acid ionomer to the isopropanol are not changed. The microporous catalyst layer of the fuel cell for the space power supply is high in catalytic activity and durability, and water generated by the catalyst layer can be directionally discharged, so that the water management capability of a membrane electrode under a space microgravity condition is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fuel cells, and in particular to a microporous catalytic layer of a fuel cell for a space power source and a preparation method thereof. Background Art

[0002] Proton exchange membrane fuel cell (PEMFC) is an efficient and environmentally friendly energy conversion device that directly converts the chemical energy of hydrogen and oxygen into electrical energy. Its energy conversion efficiency is as high as 50-60%. It is small in size and light in weight, and the byproduct water can be used for drinking by astronauts. In addition, the waste heat discharged from the fuel cell system has a temperature of about 50-70℃, which can be used for thermal management of spacecraft. Therefore, fuel cell power has great application prospects in space stations, manned spacecraft, lunar bases and other fields.

[0003] Membrane Electrode Assembly (MEA) is the core component of PEMFC. It is the multiphase material transfer and electrochemical reaction site for energy conversion. It involves three-phase interface reaction and complex mass transfer and heat transfer process, which directly determines the performance, life and cost of PEMFC. The catalyst layer plays a vital role in proton exchange membrane fuel cells. It is usually composed of catalyst, carbon carrier, ionomer and pores. These components together form a porous structure to promote the electrochemical reaction of hydrogen and oxygen at the anode and cathode. However, the existing space hydrogen and oxygen fuel cells use pure oxygen as the reactant, with a small flow rate, and the product water cannot be discharged from the reaction zone in time, which is easy to cause flooding, affecting the mass transfer of the catalyst layer, and then causing battery failure. Therefore, there is an urgent need for a battery catalyst layer structure with strong water management ability to improve the water transport problem of the membrane electrode. Summary of the invention

[0004] In order to solve the problems in the above-mentioned background technology, the first object of the present invention is to provide a microporous catalytic layer for a fuel cell for space power supply, which has high catalytic activity and strong durability. The water generated by the catalytic layer can be discharged in a direction, which can enhance the water management ability of the membrane electrode under microgravity conditions in space.

[0005] The solution adopted by the present invention to solve the technical problem is: a microporous catalyst layer of a fuel cell for a space power source, comprising an anode catalyst slurry and a cathode catalyst slurry, wherein the cathode catalyst slurry comprises a Pt / metal oxide catalyst, a perfluorosulfonic acid ionomer, ultrapure water and isopropanol;

[0006] The anode catalyst slurry comprises IrO2-Pt / metal oxide catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol; the IrO2-Pt / metal oxide catalyst comprises a metal oxide carrier and IrO2, and the surface of the metal oxide carrier carries Pt nanoparticles;

[0007] The particle sizes of the Pt / metal oxide catalyst and the IrO2-Pt / metal oxide catalyst are distributed in a gradient manner in the catalytic layer; the mass ratios of the perfluorosulfonic acid ionomer and the metal oxide carrier in the anode catalyst slurry and the cathode catalyst slurry are distributed in a gradient manner in the catalytic layer, wherein the mass ratios of the perfluorosulfonic acid ionomer and ultrapure water and isopropanol remain unchanged.

[0008] Preferably, the particle size of the IrO2-Pt / metal oxide catalyst is 10 to 200 nm.

[0009] Preferably, the I / C ratio is 0.6 to 1.5.

[0010] The second object of the present invention is to provide a method for preparing a microporous catalytic layer of a fuel cell for a space power source, comprising the following steps:

[0011] Step 1: Preparation of metal oxide support

[0012] S1. dissolving a metal oxide precursor in an acid solution to form a metal ion solution, and then adding ionized water to the metal ion solution until the concentration of the metal ions in the metal ion solution is 0.1 to 1 mol / L;

[0013] S2. using an alkaline solution as a precipitant, adding it dropwise to the metal ion solution until the metal ions in the solution are completely precipitated, then filtering, washing and collecting the resulting precipitate, and then thermally decomposing the collected precipitate to obtain a metal oxide carrier;

[0014] Step 2: Preparation of Pt / metal oxide catalyst and IrO2-Pt / metal oxide catalyst

[0015] S1. Weigh the metal oxide carrier, platinum precursor, reducing agent and solvent respectively, mix the platinum precursor, reducing agent and solvent evenly to obtain a mixed solution, then add the metal oxide carrier to the mixed solution, then stir for 30 minutes, and then perform ultrasound for 30 minutes to obtain a reaction solution, and then add an alkaline solution to the reaction solution until the pH of the reaction solution is 9;

[0016] S2. The reaction solution after adjusting the pH is placed in a sealed autoclave and reacted at 120°C for 6 hours to obtain a yellow transparent solution, which is then allowed to stand and cool, and a 5% HNO3 aqueous solution is then dropped into the solution until the pH of the yellow transparent solution is less than 5, followed by 15 minutes of ultrasonic treatment, and then filtered and the obtained powder is collected, and the obtained powder is placed in a vacuum oven and dried for 12 hours to obtain a Pt / metal oxide catalyst;

[0017] S3. The Pt / metal oxide catalyst and I rO2 are placed in a ball mill and mixed evenly to obtain an I rO2-Pt / metal oxide catalyst, wherein the particle size of the Pt / metal oxide catalyst is 10 nm to 1 μm;

[0018] Step 3: Preparation of catalyst slurry

[0019] S1. Weigh IrO2-Pt / metal oxide catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol and mix them evenly to form an anode catalyst slurry;

[0020] S2. Weigh the Pt / metal oxide catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol and mix them evenly to form a cathode catalyst slurry;

[0021] Step 4: Preparation of gradient catalytic layer

[0022] Spraying the anode catalyst slurry onto the surface of the proton exchange membrane, wherein the ratio of the IrO2-Pt / metal oxide catalyst, ultrapure water and isopropanol remains unchanged, and the particle size of the IrO2-Pt / metal oxide catalyst increases gradually in a direction away from one side of the proton exchange membrane, and the mass ratio of the perfluorosulfonic acid ionomer to the metal oxide carrier decreases gradually;

[0023] The cathode catalyst slurry is sprayed onto the other side of the proton exchange membrane surface, wherein the ratio of Pt / metal oxide catalyst, ultrapure water and isopropanol remains unchanged, and the particle size of the IrO2-Pt / metal oxide catalyst increases and the mass ratio of the perfluorosulfonic acid ionomer to the metal oxide carrier decreases in the direction away from the proton exchange membrane.

[0024] Preferably, the metal oxide precursor in step 1 is one or more of a cerium salt solution, a titanium salt solution, and a zirconium salt solution.

[0025] Preferably, the platinum precursor in step 2 is one or more of chloroplatinic acid, tetraaminoplatinum nitrate, and platinum phthalocyanine.

[0026] The above preparation method can produce a catalytic layer with excellent performance and stable structure.

[0027] The third object of the present invention is to provide a membrane electrode for a fuel cell for a space power source, comprising a proton exchange membrane, a gas diffusion layer and a catalyst layer, wherein the thickness of the catalyst layer is 500nm to 20μm, and the catalyst loading in the catalyst layer is 0.05 to 0.5mg / cm 2 .

[0028] The catalyst layer of the present application is cured on the surface of the proton exchange membrane by spraying, and the gas diffusion layer is fixed on the cathode layer and the anode layer surface of the catalyst layer by hot pressing.

[0029] A fourth object of the present invention is to provide a fuel cell for space power supply.

[0030] In this application, the stability and electrocatalytic activity of the battery are further improved by combining Pt / metal oxide catalyst with IrO2, and the anti-reverse polarity effect of IrO2 is combined to reduce the influence of the space microgravity environment on the gas-liquid distribution and flow inside the battery, thereby improving the stability and life of the battery;

[0031] Secondly, by having a gradient distribution of the particle sizes of the Pt / metal oxide catalyst and the IrO2-Pt / metal oxide catalyst in the catalytic layer and a gradient distribution of the mass ratio of the perfluorosulfonic acid ionomer to the metal oxide carrier in the anode catalyst slurry and the cathode catalyst slurry in the catalytic layer, directional flow of water under capillary pressure is achieved, thereby meeting the specific water management requirements of the battery under microgravity conditions in space.

[0032] In summary, the beneficial effects of the present invention are:

[0033] The catalytic layer of the present invention can improve the drainage capacity of the membrane electrode, based on the principle of micropore fluid dynamics, combined with the improvement of the surface properties of the catalyst, to achieve directional flow of water under capillary pressure, and meet the specific water management requirements of the battery under space microgravity conditions;

[0034] By increasing the thickness of the catalyst layer and the structural arrangement without affecting the battery performance, the density of active sites in the catalyst layer is effectively increased, the drainage capacity of the catalyst layer is improved, the concentration polarization is reduced, and the battery power density is improved;

[0035] By regulating the structure within the catalyst layer, the design of the water vapor transmission path is strengthened, the slurry solidification molding process is studied, and the three-phase reaction interface of the catalyst layer is regulated to construct an electrode structure with high transmission flux and high catalyst utilization.

[0036] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the following specifically cites a preferred embodiment and describes it in detail with the accompanying drawings as follows. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a comparison chart of polarization performance, voltage (Vo ltage / V) and current density (Current Dens ity / A / cm 2 ) relationship diagram.

[0038] Figure 2This is a comparison chart of polarization performance after accelerated durability test, voltage (Vo ltage / V) and current density (Current Dens ity / A / cm 2 ) relationship diagram. DETAILED DESCRIPTION

[0039] In order to make the content of the present invention more clearly understood, the present invention is further described below based on specific embodiments in conjunction with the accompanying drawings.

[0040] A microporous catalyst layer for a fuel cell used in a space power supply, wherein the cathode catalyst slurry comprises a Pt / metal oxide catalyst, a perfluorosulfonic acid ionomer, ultrapure water and isopropanol;

[0041] The anode catalyst slurry comprises IrO2-Pt / metal oxide catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol; the IrO2-Pt / metal oxide catalyst comprises a metal oxide carrier and IrO2, and the surface of the metal oxide carrier carries Pt nanoparticles;

[0042] The particle sizes of the Pt / metal oxide catalyst and the IrO2-Pt / metal oxide catalyst are distributed in a gradient manner in the catalytic layer; the mass ratios of the perfluorosulfonic acid ionomer and the metal oxide carrier in the anode catalyst slurry and the cathode catalyst slurry are distributed in a gradient manner in the catalytic layer, wherein the mass ratios of the perfluorosulfonic acid ionomer and ultrapure water and isopropanol remain unchanged.

[0043] Preferably, the particle size of the Pt / metal oxide catalyst is 10 to 200 nm.

[0044] Preferably, the I / C ratio is 0.6 to 1.5.

[0045] A method for preparing a microporous catalytic layer of a fuel cell for a space power source comprises the following steps:

[0046] Step 1: Preparation of metal oxide support

[0047] S1. dissolving a metal oxide precursor in an acid solution to form a metal ion solution, and then adding ionized water to the metal ion solution until the concentration of the metal ions in the metal ion solution is 0.1 to 1 mol / L;

[0048] S2. Use an alkaline solution as a precipitant and add it dropwise to the metal ion solution until the metal ions in the solution are completely precipitated, then filter, wash and collect the resulting precipitate, and then thermally decompose the collected precipitate to obtain a metal oxide carrier.

[0049] The acid solution used in the above steps is not particularly limited, and can be one or a mixture of acid solutions such as sulfuric acid, hydrochloric acid, nitric acid, etc.

[0050] The alkaline solution used in the above steps is not particularly limited, and can be one or a mixture of two alkaline solutions such as sodium hydroxide, ammonia water, ammonium carbonate, potassium hydroxide, etc.

[0051] Step 2: Preparation of Pt / metal oxide catalyst and IrO2-Pt / metal oxide catalyst

[0052] S1. Weigh the metal oxide carrier, platinum precursor, reducing agent and solvent respectively, mix the platinum precursor, reducing agent and solvent evenly to obtain a mixed solution, then add the metal oxide carrier to the mixed solution, then stir for 30 minutes, and then perform ultrasound for 30 minutes to obtain a reaction solution, and then add an alkaline solution to the reaction solution until the pH of the reaction solution is 9;

[0053] S2. The reaction solution after adjusting the pH is placed in a sealed autoclave and reacted at 120°C for 6 hours to obtain a yellow transparent solution, which is then allowed to stand and cool, and a 5% HNO3 aqueous solution is then dropped into the solution until the pH of the yellow transparent solution is less than 5, followed by 15 minutes of ultrasonic treatment, and then filtered and the obtained powder is collected, and the obtained powder is placed in a vacuum oven and dried for 12 hours to obtain a Pt / metal oxide catalyst;

[0054] S3. Put the Pt / metal oxide catalyst and IrO2 into a ball mill and mix them evenly to obtain IrO2-Pt / metal oxide catalyst. The particle size of the Pt / metal oxide catalyst is 10nm~1μm.

[0055] Step 3: Preparation of catalyst slurry

[0056] S1. Weigh IrO2-Pt / metal oxide catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol and mix them evenly to form an anode catalyst slurry;

[0057] S2. Weigh the Pt / metal oxide catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol and mix them evenly to form a cathode catalyst slurry;

[0058] Step 4: Preparation of gradient catalytic layer

[0059] Spraying the anode catalyst slurry onto the surface of the proton exchange membrane, wherein the ratio of the IrO2-Pt / metal oxide catalyst, ultrapure water and isopropanol remains unchanged, and the particle size of the IrO2-Pt / metal oxide catalyst increases gradually in a direction away from one side of the proton exchange membrane, and the mass ratio of the perfluorosulfonic acid ionomer to the metal oxide carrier decreases gradually;

[0060] The cathode catalyst slurry is sprayed onto the other side of the proton exchange membrane surface, wherein the ratio of Pt / metal oxide catalyst, ultrapure water and isopropanol remains unchanged, and the particle size of the IrO2-Pt / metal oxide catalyst increases and the mass ratio of the perfluorosulfonic acid ionomer to the metal oxide carrier decreases in the direction away from the proton exchange membrane.

[0061] The metal oxide precursor in step 1 is preferably but not limited to one or more of a cerium salt solution, a titanium salt solution, and a zirconium salt solution.

[0062] The platinum precursor in step 2 is preferably but not limited to one or more of chloroplatinic acid, tetraaminoplatinum nitrate, and platinum phthalocyanine.

[0063] A membrane electrode for a fuel cell for space power supply, comprising a proton exchange membrane, a gas diffusion layer and a catalyst layer, wherein the catalyst layer is a microporous catalyst layer for a fuel cell for space power supply according to any one of claims 1 to 3, the thickness of the catalyst layer is 500nm to 20μm, and the catalyst loading in the catalyst layer is 0.05 to 0.5mg / cm 2 .

[0064] The perfluorosulfonic acid ionomer used in the following examples and comparative examples is specifically D520 ionomer.

[0065] Embodiment 1

[0066] Step 1: Preparation of TiO2 carrier

[0067] S1. Dissolving titanium tetrachloride in an acid solution of pH <1, and then adding deionized water to obtain a metal ion solution;

[0068] The above method is used to prepare metal ion solutions with titanium metal ion concentrations of 0.1 mol / L, 0.3 mol / L, 0.5 mol / L and 0.7 mol / L respectively;

[0069] S2. Ammonia water is used as a precipitant and is added dropwise to the metal ion solution until the pH of the solution is adjusted to 9, and then stirred evenly. The metal ion solution is then placed in a centrifuge and centrifuged at a speed of 4000r / min for 10 minutes. The precipitate is collected and then washed with ethanol and deionized water. The washed precipitate is then placed in a tubular furnace for calcination at a temperature of 350°C for 30 minutes to obtain a TiO2 carrier.

[0070] TiO2 carriers numbered TA, TB, TC and TD were prepared respectively using the above-mentioned metal ion solutions with titanium metal ion concentrations of 0.1 mol / L, 0.3 mol / L, 0.5 mol / L and 0.7 mol / L, and the particle sizes of TiO2 carriers with different numbers were different.

[0071] Step 2: Preparation of IrO2-Pt / TiO2 catalyst and Pt / TiO2 catalyst

[0072] S1. Pour the sodium citrate solid into a 50ml beaker, then add 10ml ethylene glycol to completely dissolve the sodium citrate solid, then dissolve 1g H2PtC l6.6H2O in 50ml ethylene glycol, wherein the molar ratio of sodium citrate to Pt is 2.5:1. Add 400mg CeO2 carrier to the above ethylene glycol solution containing H2PtC l6, ultrasonicate for 0.5h, and then stir for 0.5h to obtain a reaction solution, and then adjust the pH value of the reaction solution to 9 with a 5% by weight KOH / EG solution;

[0073] S2. The reaction solution after adjusting the pH is placed in a sealed autoclave and reacted at 120°C for 6 hours to obtain a yellow transparent solution, which is then allowed to stand and cool, and a 5% HNO3 aqueous solution is then dropped into the solution until the pH of the yellow transparent solution is less than 5, followed by 15 minutes of ultrasonic treatment, and then filtered and the resulting powder is collected, and the resulting powder is placed in a vacuum oven and dried for 12 hours to obtain a Pt / TiO2 catalyst;

[0074] In the S1 process of step 2, Pt / TiO2 catalysts numbered PT-A, PT-B, PT-C and PT-D can be obtained respectively by adding TiO2 carriers numbered TA, TB, TC and TD;

[0075] S3. The Pt / TiO2 catalyst obtained in the above step and 1wt% IrO2 were placed in a ball mill and mixed and dispersed for 3 hours to obtain IrO2-Pt / TiO2 catalyst.

[0076] Among them, in the S3 process of step 2, by adding Pt / TiO2 catalysts numbered PT-A, PT-B, PT-C and PT-D, IrO2-Pt / TiO2 catalysts numbered PTI-A, PTI-B, PTI-C and PTI-D can be obtained respectively.

[0077] Step 3: Preparation of catalyst slurry

[0078] S1. PTI-A catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:40:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered An.A;

[0079] PTI-B catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:35:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered An.B;

[0080] PT IC catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:30:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered An.C;

[0081] PT ID catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:25:30:90, dispersed for 3 hours by ball milling and mixed evenly, and then dispersed for 30 minutes by a high-speed shearing machine to form a catalyst slurry numbered An.D.

[0082] An.A, An.B, An.C and An.D catalyst slurries are anode catalyst slurries.

[0083] S1. PT-A catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:40:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered Ca.A;

[0084] PT-B catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:35:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered Ca.B;

[0085] PT-C catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:30:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered Ca.C;

[0086] PT-D catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:25:30:90, dispersed for 3 hours by ball milling and mixed evenly, and then dispersed for 30 minutes by a high-speed shearing machine to form a catalyst slurry numbered Ca.D.

[0087] Ca.A, Ca.B, Ca.C and Ca.D catalyst slurries are cathode catalyst slurries.

[0088] Step 4: Preparation of gradient catalytic layer

[0089] Ca.A, Ca.B, Ca.C and Ca.D were sprayed onto the surface of the proton exchange membrane in sequence until the Pt loading of the catalyst layer reached 0.4 mg / cm 2 After drying, the An.A, An.B, An.C and An.D slurries are sprayed onto the other surface of the proton exchange membrane in sequence until the catalyst Pt loading reaches 0.1 mg / cm 2 ; A gradient catalytic layer (CCM) is obtained.

[0090] The method for manufacturing the membrane electrode is to fix the JNTG gas diffusion layer on the surface of the cathode layer and the anode layer of the CCM by hot pressing.

[0091] Embodiment 2

[0092] Step 1: Preparation of CeO2 carrier

[0093] S1. dissolving cerium nitrate hexahydrate in deionized water to obtain a metal ion solution;

[0094] The metal ion solutions with the concentrations of cerium metal ions were prepared by the above method at 0.1 mol / L, 0.3 mol / L, 0.5 mol / L and 0.7 mol / L respectively;

[0095] S2. Use 10% ammonia water as a precipitant, add it dropwise into the metal ion solution until a stable and uniform solution is formed, stir it with an electric stirrer for 12 hours, place it in a refrigerator for aging for 12 hours, then place the metal ion solution in a centrifuge and centrifuge it at a centrifugal speed of 4000r / min for 10 minutes, collect the precipitate, then wash the obtained precipitate with ethanol and deionized water, and then place the washed precipitate in a tubular furnace for calcination at a temperature of 400°C and a calcination time of 40 minutes to obtain a CeO2 carrier.

[0096] CeO2 carriers numbered CA, CB, CC and CD were prepared respectively using the above-mentioned metal ion solutions with cerium metal ion concentrations of 0.1 mol / L, 0.3 mol / L, 0.5 mol / L and 0.7 mol / L, and the particle sizes of CeO2 carriers with different numbers were different.

[0097] Step 2: Preparation of IrO2-Pt / CeO2 catalyst and Pt / CeO2 catalyst

[0098] S1. Pour the sodium citrate solid into a 50ml beaker, then add 10ml ethylene glycol (EG) to completely dissolve the sodium citrate solid, then dissolve 1g H2PtCl6.6H2O in 50ml ethylene glycol, wherein the molar ratio of sodium citrate to Pt is 2.5:1. Add 400mg CeO2 carrier to the above ethylene glycol solution containing H2PtCl6, ultrasonicate for 0.5h, and stir for 0.5h to obtain a reaction solution, and then adjust the pH value of the reaction solution to 9 with a 5% by weight KOH / EG solution;

[0099] S2. The reaction solution after adjusting the pH is placed in a sealed autoclave and reacted at 120°C for 6 hours to obtain a yellow transparent solution, which is then allowed to stand and cool, and a 5% HNO3 aqueous solution is then dropped into the solution until the pH of the yellow transparent solution is less than 5, followed by 15 minutes of ultrasonic treatment, and then filtered and the resulting powder is collected, and the resulting powder is placed in a vacuum oven and dried for 12 hours to obtain a Pt / CeO2 catalyst;

[0100] In the S1 process of step 2, Pt / CeO2 catalysts numbered PC-A, PC-B, PC-C and PC-D can be obtained respectively by adding CeO2 carriers numbered CA, CB, CC and CD;

[0101] S3. The Pt / CeO2 catalyst obtained in the above step and 1wt% IrO2 were placed in a ball mill and mixed for 3 hours to obtain an IrO2-Pt / CeO2 catalyst.

[0102] Among them, in the S3 process of step 2, by adding Pt / CeO2 catalysts numbered PC-A, PC-B, PC-C and PC-D, IrO2-Pt / CeO2 catalysts numbered PCI-A, PCI-B, PCI-C and PCI-D can be obtained respectively.

[0103] Step 3: Preparation of catalyst slurry

[0104] S1. PCI-A catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:40:30:90, dispersed by ball milling for 3 hours, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered An.A;

[0105] PCI-B catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:35:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered An.B;

[0106] PCI-C catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:30:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered An.C;

[0107] PCI-D catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:25:30:90, dispersed for 3 hours by ball milling and mixed evenly, and then dispersed for 30 minutes by a high-speed shearing machine to form a catalyst slurry numbered An.D.

[0108] An.A, An.B, An.C and An.D catalyst slurries are anode catalyst slurries.

[0109] S1. PC-A catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:40:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered Ca.A;

[0110] PC-B catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:35:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered Ca.B;

[0111] PC-C catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:30:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered Ca.C;

[0112] PC-D catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:25:30:90, dispersed for 3 hours by ball milling and mixed evenly, and then dispersed for 30 minutes by a high-speed shearing machine to form a catalyst slurry numbered Ca.D.

[0113] Ca.A, Ca.B, Ca.C and Ca.D catalyst slurries are cathode catalyst slurries.

[0114] Step 4: Preparation of gradient catalytic layer

[0115] Ca.A, Ca.B, Ca.C and Ca.D were sprayed onto the surface of the proton exchange membrane in sequence until the Pt loading of the catalyst layer reached 0.4 mg / cm 2After drying, the An.A, An.B, An.C and An.D slurries are sprayed onto the other surface of the proton exchange membrane in sequence until the catalyst Pt loading reaches 0.1 mg / cm 2 ; A gradient catalytic layer (CCM) is obtained.

[0116] The method for manufacturing the membrane electrode is to fix the JNTG gas diffusion layer on the surface of the cathode layer and the anode layer of the CCM by hot pressing.

[0117] Embodiment 3

[0118] Step 1: Preparation of TiO2-SnO2 carrier

[0119] S1. dissolving titanium tetrachloride and SnCl4·5H2O in deionized water to obtain a metal ion solution, wherein the molar ratio of Sn and Ti ions in the metal ion solution is 1:1;

[0120] The metal ion solutions with the concentrations of Sn metal ions were prepared by the above method at 0.1 mol / L, 0.3 mol / L, 0.5 mol / L and 0.7 mol / L respectively;

[0121] S2. Use 10% ammonia water as a precipitant, add it dropwise into the metal ion solution until a stable and uniform solution is formed, stir it with an electric stirrer for 12 hours, place it in a refrigerator for aging for 12 hours, then place the metal ion solution in a centrifuge and centrifuge it at a centrifugal speed of 4000r / min for 10 minutes, collect the precipitate, then wash the obtained precipitate with ethanol and deionized water, and then place the washed precipitate in a tubular furnace for calcination at a temperature of 400°C and a calcination time of 40 minutes to obtain a TiO2-SnO2 carrier.

[0122] TiO2-SnO2 carriers numbered TS-A, TS-B, TS-TS and TS-D were prepared respectively using the above-mentioned metal ion solutions with Sn metal ion concentrations of 0.1 mol / L, 0.3 mol / L, 0.5 mol / L and 0.7 mol / L, and the particle sizes of the TiO2-SnO2 carriers with different numbers were different.

[0123] Step 2: Preparation of IrO2-Pt / TiO2-SnO2 catalyst and Pt / TiO2-SnO2 catalyst

[0124] S1. Pour the sodium citrate solid into a 50 ml beaker, then add 10 ml ethylene glycol (EG) to completely dissolve the sodium citrate solid, and then dissolve 1 g H2PtCl6.6H2O in 50 ml ethylene glycol, wherein the molar ratio of sodium citrate to Pt is 2.5:1. Add 400 mg TiO2-SnO2 carrier to the above ethylene glycol solution containing H2PtCl6, ultrasonicate for 0.5 h, and stir for 0.5 h to obtain a reaction solution, and then adjust the pH value of the reaction solution to 9 with a 5% by weight KOH / EG solution;

[0125] S2. The reaction solution after adjusting the pH is placed in a sealed autoclave and reacted at 120°C for 6 hours to obtain a yellow transparent solution, which is then allowed to stand and cool, and a 5% HNO3 aqueous solution is then dropped into the solution until the pH of the yellow transparent solution is less than 5, followed by 15 minutes of ultrasonic treatment, and then filtered and the resulting powder is collected, and the resulting powder is placed in a vacuum oven and dried for 12 hours to obtain a Pt / TiO2-SnO2 catalyst;

[0126] In the S1 process of step 2, TSeO2 carriers numbered TS-A, TS-B, TS-TS and TS-D are added to obtain PTS / TSeO2 catalysts numbered PTS-A, PTS-B, PTS-TS and PTS-D respectively;

[0127] S3. The Pt / TiO2-SnO2 catalyst obtained in the above step and 1wt% IrO2 were placed in a ball mill and mixed and dispersed for 3 hours to obtain IrO2-Pt / TiO2-SnO2 catalyst.

[0128] Among them, in the S3 process of step 2, by adding Pt / TiO2-SnO2 catalysts numbered PTS-A, PTS-B, PTS-TS and PTS-D, IrO2-Pt / TiO2-SnO2 catalysts numbered PTS IA, PTS IB, PTS I-TS and PTS ID can be obtained respectively.

[0129] Step 3: Preparation of catalyst slurry

[0130] S1. PTS IA catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:40:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered An.A;

[0131] PTS IB catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:35:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered An.B;

[0132] PTS IC catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:30:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered An.C;

[0133] PTS ID catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:25:30:90, dispersed for 3 hours by ball milling and mixed evenly, and then dispersed for 30 minutes by a high-speed shearing machine to form a catalyst slurry numbered An.D.

[0134] An.A, An.B, An.C and An.D catalyst slurries are anode catalyst slurries.

[0135] S1. PTS-A catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:40:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered Ca.A;

[0136] PTS-B catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:35:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered Ca.B;

[0137] PTS-C catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:30:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered Ca.C;

[0138] PTS-D catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:25:30:90, dispersed for 3 hours by ball milling and mixed evenly, and then dispersed for 30 minutes by a high-speed shearing machine to form a catalyst slurry numbered Ca.D.

[0139] Ca.A, Ca.B, Ca.C and Ca.D catalyst slurries are cathode catalyst slurries.

[0140] Step 4: Preparation of gradient catalytic layer

[0141] Ca.A, Ca.B, Ca.C and Ca.D were sprayed onto the surface of the proton exchange membrane in sequence until the Pt loading of the catalyst layer reached 0.4 mg / cm 2 After drying, the An.A, An.B, An.C and An.D slurries are sprayed onto the other surface of the proton exchange membrane in sequence until the catalyst Pt loading reaches 0.1 mg / cm 2 , obtaining a gradient catalytic layer (CCM).

[0142] The method for manufacturing the membrane electrode is to fix the JNTG gas diffusion layer on the surface of the cathode layer and the anode layer of the CCM by hot pressing.

[0143] Comparative Example 1

[0144] Step 1: Preparation of IrO2-Pt / C catalyst and Pt / C catalyst

[0145] The Pt / C catalyst and 1wt% IrO2 were placed in a ball mill and mixed and dispersed for 3 hours to obtain an IrO2-Pt / C catalyst.

[0146] Step 3: Preparation of catalyst slurry

[0147] S1. IrO2-Pt / C, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:30:30:90, dispersed by ball milling for 3 hours and mixed evenly, and then dispersed by a high-speed shearing machine for 30 minutes to form a catalyst slurry numbered An.0;

[0148] S2. Pt / C, perfluorosulfonic acid ionomer, ultrapure water and isopropanol were weighed and mixed in a mass ratio of 1:30:30:90, dispersed by ball milling for 3 h and mixed evenly, and then dispersed by a high-speed shearing machine for 30 min to form a catalyst slurry numbered Ca.0;

[0149] Step 4: Preparation of gradient catalytic layer

[0150] Ca.0 was sprayed onto the surface of the proton exchange membrane until the Pt loading of the catalyst layer reached 0.4 mg / cm 2 After drying, the An.0 slurry is sprayed onto the other surface of the proton exchange membrane until the catalyst Pt loading reaches 0.1 mg / cm 2 , obtaining a gradient catalytic layer (CCM).

[0151] The method for manufacturing the membrane electrode is to fix the JNTG gas diffusion layer on the surface of the cathode layer and the anode layer of the CCM by hot pressing.

[0152] The embodiments described above are only preferred implementation modes of the present invention and cannot be used to limit the protection scope of the present invention. Any non-substantial changes and modifications made by those skilled in the art on the basis of the invention shall fall within the protection scope of the present invention.

Claims

1. A microporous catalyst layer for a fuel cell used as a space power source, comprising an anode catalyst slurry and a cathode catalyst slurry, characterized in that: The cathode catalyst slurry comprises a Pt / metal oxide catalyst, a perfluorosulfonic acid ionomer, ultrapure water and isopropanol; The anode catalyst slurry comprises an IrO2-Pt / metal oxide catalyst, a perfluorosulfonic acid ionomer, ultrapure water and isopropanol; the IrO2-Pt / metal oxide catalyst comprises a metal oxide carrier and IrO2, and the surface of the metal oxide carrier carries Pt nanoparticles; The particle sizes of the Pt / metal oxide catalyst and the IrO2-Pt / metal oxide catalyst are distributed in a gradient manner in the catalytic layer; the mass ratios of the perfluorosulfonic acid ionomer and the metal oxide carrier in the anode catalyst slurry and the cathode catalyst slurry are distributed in a gradient manner in the catalytic layer, wherein the mass ratios of the perfluorosulfonic acid ionomer and ultrapure water and isopropanol remain unchanged.

2. The microporous catalyst layer of a fuel cell for a space power source according to claim 1, characterized in that: The particle size of the Pt / metal oxide catalyst is 10 to 200 nm.

3. The microporous catalyst layer of a fuel cell for a space power source according to claim 1, characterized in that: The mass ratio of the perfluorosulfonic acid ionomer to the metal oxide carrier is 0.6 to 1.

5.

4. A method for preparing a microporous catalyst layer of a fuel cell for a space power source according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: Preparation of metal oxide support S1. preparing a metal ion solution, and then adding ionized water to the metal ion solution until the concentration of the metal ions in the metal ion solution is 0.1 to 1 mol / L; S2. using an alkaline solution as a precipitant, adding it dropwise to the metal ion solution until the metal ions in the solution are completely precipitated, then filtering, washing and collecting the resulting precipitate, and then thermally decomposing the collected precipitate to obtain a metal oxide carrier; Step 2: Preparation of Pt / metal oxide catalyst and IrO2-Pt / metal oxide catalyst S1. Weigh the metal oxide carrier, platinum precursor, reducing agent and solvent respectively, mix the platinum precursor, reducing agent and solvent evenly to obtain a mixed solution, then add the metal oxide carrier to the mixed solution, then stir for 30 minutes, and then perform ultrasound for 30 minutes to obtain a reaction solution, and then add an alkaline solution to the reaction solution until the pH of the reaction solution is 9; S2. The reaction solution after adjusting the pH is placed in a sealed autoclave and reacted at 120°C for 6 hours to obtain a yellow transparent solution, which is then allowed to stand and cool, and a 5% HNO3 aqueous solution is then dropped into the solution until the pH of the yellow transparent solution is less than 5, followed by 15 minutes of ultrasonic treatment, and then filtered and the obtained powder is collected, and the obtained powder is placed in a vacuum oven and dried for 12 hours to obtain a Pt / metal oxide catalyst; S3. The Pt / metal oxide catalyst and IrO2 are placed in a ball mill and mixed evenly to obtain an I rO2-Pt / metal oxide catalyst, wherein the particle size of the Pt / metal oxide catalyst is 10nm to 1μm; Step 3: Preparation of catalyst slurry S1. Weigh IrO2-Pt / metal oxide catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol and mix them evenly to form an anode catalyst slurry; S2. Weigh the Pt / metal oxide catalyst, perfluorosulfonic acid ionomer, ultrapure water and isopropanol and mix them evenly to form a cathode catalyst slurry; Step 4: Preparation of gradient catalytic layer Spraying the anode catalyst slurry onto the surface of the proton exchange membrane, wherein the ratio of IrO2-Pt / metal oxide catalyst, ultrapure water and isopropanol remains unchanged, and the particle size of the IrO2-Pt / metal oxide catalyst increases gradually in a direction away from one side of the proton exchange membrane, and the mass ratio of the perfluorosulfonic acid ionomer to the metal oxide carrier decreases gradually; The cathode catalyst slurry is sprayed onto the other side of the proton exchange membrane surface, wherein the ratio of Pt / metal oxide catalyst, ultrapure water and isopropanol remains unchanged, and the particle size of IrO2-Pt / metal oxide catalyst increases and the mass ratio of perfluorosulfonic acid ionomer to metal oxide carrier decreases in the direction away from the proton exchange membrane side.

5. The method for preparing a microporous catalyst layer of a fuel cell for a space power source according to claim 4, characterized in that: The metal oxide precursor in step 1 is one or more of a cerium salt solution, a titanium salt solution, and a zirconium salt solution.

6. The method for preparing a microporous catalytic layer of a fuel cell for a space power source according to claim 4, characterized in that: The platinum precursor in step 2 is one or more of chloroplatinic acid, tetraaminoplatinum nitrate, and platinum phthalocyanine.

7. A membrane electrode for a fuel cell for space power, comprising a proton exchange membrane, a gas diffusion layer and a catalyst layer, wherein the catalyst layer is a microporous catalyst layer for a fuel cell for space power according to any one of claims 1 to 3, the thickness of the catalyst layer is 500 nm to 20 μm, and the catalyst loading in the catalyst layer is 0.05 to 0.5 mg / cm 2 .

8. A fuel cell for space power supply, characterized in that: Comprising the membrane electrode as claimed in claim 7.

Citation Information

Patent Citations

  • An anti-erosion fuel battery catalyzer and its making method

    CN101087023A

  • Membrane electrode containing gradient cathode catalyst layer and preparation method and application thereof

    CN115133043A

  • Anode catalyst layer and preparation method thereof, membrane electrode and fuel cell

    CN115172779A

  • Metal oxide carrier as well as preparation method and application thereof

    CN115784294A

  • Anode catalyst slurry, catalyst coating film, preparation method of catalyst coating film and membrane electrode

    CN117004987A